2016
DOI: 10.1634/theoncologist.2015-0501
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Bevacizumab in Combination With Temozolomide as First-Line Treatment in Patients With Metastatic Uveal Melanoma

Abstract: Lessons LearnedTrials dedicated to metastatic uveal melanoma are needed because of the poor prognosis of this rare cancer and because its biology is distinct from that of cutaneous melanoma.Agents targeting the MEK/ERK/MAP kinase pathways are being tested.Background.In experimental models, bevacizumab suppressed in vitro growth and in vivo hepatic metastasis of ocular melanoma cells. Additional preclinical data suggested a potential benefit when combining bevacizumab with dacarbazine.Methods.This noncomparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
0
35
1
1
Order By: Relevance
“…Reasons for data not being available included a lack of investigator response to requests for data and archived data that were no longer available. Of the 29 studies for which data were available, 5 involved immunotherapy [27][28][29][30][31], 7 involved a kinase inhibitor (of which 2 were randomised studies against temozolomide or dacarbazine, respectively) [12,[32][33][34][35][36], 2 used an anti-angiogenic agent [37,38], 8 involved chemotherapy (1 of which was a randomised study of intrahepatic versus intravenous chemotherapy) [39][40][41][42][43][44][45] and 7 studies involved intrahepatic treatment (chemotherapy or immunotherapy) [46][47][48][49][50][51][52] (supplementary Table S1, available at Annals of Oncology online).…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for data not being available included a lack of investigator response to requests for data and archived data that were no longer available. Of the 29 studies for which data were available, 5 involved immunotherapy [27][28][29][30][31], 7 involved a kinase inhibitor (of which 2 were randomised studies against temozolomide or dacarbazine, respectively) [12,[32][33][34][35][36], 2 used an anti-angiogenic agent [37,38], 8 involved chemotherapy (1 of which was a randomised study of intrahepatic versus intravenous chemotherapy) [39][40][41][42][43][44][45] and 7 studies involved intrahepatic treatment (chemotherapy or immunotherapy) [46][47][48][49][50][51][52] (supplementary Table S1, available at Annals of Oncology online).…”
Section: Resultsmentioning
confidence: 99%
“…Selumetinib is also being tested in combination with temozolomide (NCT01143402), and the maximum tolerated dose of intermittent selumetinib is being investigated (NCT02768766) [69]. Bevacizumab was tested in combination with dacarbazine showing modest activity [70]. A pilot study with the kinase inhibitor sunitinib showed a potential clinical benefit that was independent of the expression level of the target kinase, c-Kit [71].…”
Section: Clinical Features Of Uveal Melanomamentioning
confidence: 99%
“…Multitargeted tyrosine kinase inhibitors such as sunitinib and sorafenib have also been tested in phase II trials (Bhatia et al., ; Mahipal et al., ; Mouriaux et al., ; Sacco et al., ), but none of these inhibitors have shown clinical benefit. Bevacizumab and aflibercept, which inhibit VEGF, have also failed to show any significant clinical benefit (Piperno‐Neumann et al., ; Tarhini et al., ). Cabozantinib, a nonspecific MET and tyrosine kinase inhibitor, was tested in a phase II trial, and the UM cohort showed 61% of patients (14/23) achieved stable disease at week 12, with median PFS of 4.8 months and median OS of 12.6 months (Daud et al., ).…”
Section: Oncogenic Signalingmentioning
confidence: 99%